If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(5 + -1x + -12) = 4(x + 2) Reorder the terms: 2x + 3(5 + -12 + -1x) = 4(x + 2) Combine like terms: 5 + -12 = -7 2x + 3(-7 + -1x) = 4(x + 2) 2x + (-7 * 3 + -1x * 3) = 4(x + 2) 2x + (-21 + -3x) = 4(x + 2) Reorder the terms: -21 + 2x + -3x = 4(x + 2) Combine like terms: 2x + -3x = -1x -21 + -1x = 4(x + 2) Reorder the terms: -21 + -1x = 4(2 + x) -21 + -1x = (2 * 4 + x * 4) -21 + -1x = (8 + 4x) Solving -21 + -1x = 8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -21 + -1x + -4x = 8 + 4x + -4x Combine like terms: -1x + -4x = -5x -21 + -5x = 8 + 4x + -4x Combine like terms: 4x + -4x = 0 -21 + -5x = 8 + 0 -21 + -5x = 8 Add '21' to each side of the equation. -21 + 21 + -5x = 8 + 21 Combine like terms: -21 + 21 = 0 0 + -5x = 8 + 21 -5x = 8 + 21 Combine like terms: 8 + 21 = 29 -5x = 29 Divide each side by '-5'. x = -5.8 Simplifying x = -5.8
| 228=w*2w+6 | | 2x-5=x+26 | | 199=x^2+2x | | 3z-4=2iz+5i | | 6.05+4.7c=3.4c-6.95 | | 3(7p-1)=7p-3 | | 16=x-y | | -6w^2+23w+4=0 | | 5x-4(-5y+5x)-3y= | | -4t+10=-6t-20 | | -25=5(4q-10)-5q | | Y=0.5x+6 | | -2x+4(1-3x)=2x-4(6x+5) | | 1-4n+3=4n-7n-2 | | 9(5b+4)= | | -(a+1)=7-a | | y+30=8 | | 0.3(x+100)+1.5=111 | | 36x-90-30x-60-3x-15=16x+24-6x+6-6+8x | | 10.19-3.3q+7.2q=2.8q-11.59 | | 3x+30=X-2 | | 3x+7x=4x-9 | | 4ab+4a= | | -6.5z+2.26=-17.74-7.5z | | -5w-(7z-6w)-2z= | | 12-m-9m=-20-12m | | x+8=1-6x | | -4w-5(-7x+4w)+6x= | | -3(x-5)-(2x+13)=-4(2x+2)+2(x-3)-2x-4x | | x+10=-y+10 | | -4(-3w-3z)-2(-6z-w)= | | 5x-2-3x=17+12x-23 |